RANCANG BANGUN MESIN PENGISI BOTOL OTOMATIS BERBASIS ARDUINO MEGA 2560 DENGAN INTERFACE NEXTION HMI - Listiana, Reni Listiana; Yurika, Yurika -; Rossi, Fattaahku Muhammad (UPPM Politeknik TEDC Bandung, 2024)
Indonesia is experiencing rapid development in the industrial sector, especially in the packaging and bottle filling industry. Research on microcontroller-based automatic bottle filling systems has also developed a lot. Reducing manufacturing costs and simplifying a working system is the goal of a process in industry, so it is necessary to design a prototype to maximize the charging system with the Arduino program without destroying accuracy in charging. With this prototype, the accuracy of the liquid volume, response time, and working system will be known so that in making this filling machine prototype, several stages are carried out including consultation, literature study, design, creation and testing of the system as well as analysis of the results obtained from testing the prototype. In this research, volume testing and total time testing for the entire system were carried out at an Arduino set point of 250 ml and an Arduino set point of 180 ml. The test process for filling 2 bottles in 1 process produces results, namely for a set point of 250 ml, it produces an average volume of 248 ml and an average total time of 57.195 seconds, while the test with a set point of 180 ml produces an average volume of 177 ml with the total average time is 47.638 seconds. So it can be stated that this prototype is capable of producing filling with relatively stable water volume results. The principle of this prototype system is simple, namely the system runs in a structured manner based on triggers from sensors and certain time intervals.